Globus pallidus neuronal firing rates relate to dystonia aetiology and outcome from Deep Brain Stimulation (DBS) in children. Issue 3 (March 2016) - McClelland, V.M.; Valentin, A.; Rey, H.G.; Lumsden, D.E.; Elze, M.C.; Selway, R.; Alarcon, G.; Lin, J.P.
Abstract : Objectives: To compare neuronal firing rates from the Globus Pallidus interna (GPi) and externa (GPe) in children undergoing DBS for different types of dystonia and to relate findings to outcome. Methods: Microelectrode data were obtained to guide electrode position in 44 children with dystonia (14 Primary, 22 Secondary Static, 8 Secondary Progressive due to Neurodegeneration and Brain Iron Accumulation (NBIA); age 3.3–18.1 years). Digitised spike trains were analysed off-line, blind to clinical data. Results: We identified 267 GPi and 87 GPe cells. Median GPi firing frequency was higher in Primary (13.5 Hz) than Secondary Static dystonia (9.6 Hz) ( p  = 0.002) and higher in NBIA (25 Hz) than either Primary ( p  = 0.006) or Secondary Static dystonia ( p  = 0.00004). Median GPe firing frequency was higher in NBIA (15.9 Hz) than Secondary Static dystonia (7 Hz) ( p  = 0.013). The proportion of regular versus irregularly firing cells also varied significantly across groups ( p  < 0.001). GPi firing frequency showed a positive correlation with 1-year outcome from DBS (percentage improvement in Burke–Fahn–Marsden Dystonia Rating Scale motor score), for the group overall ( p  = 0.040) and particularly for the non-progressive patients ( p  = 0.006). Conclusion: Pallidal firing rates differ with dystonia type and correlate with DBS outcome. This information could guide future target selection in a more individualized approach to neuromodulation.